Situational Archetype Analysis On Main Characters In Nikolaj Arcel’s The Dark Tower Film - Alfa Rina; Samanik Samanik (Journal of Arts and Education, 2023)
This study explores the study of situational archetypes and has the objective to investigate how situational archetypes are described in the main characters in The Dark Tower film. In literary work, the situational archetype is defined as the image or the character that the readers want to pursue. Situational archetypes have the function to build the character by appearing the certain condition and the situation that the main characters face in the film. By using the situational archetype, it will be explained the detail why the character may do the quest.The objectives of this study are to find situational archetype on main characters in Nicolaj Arcel’s The Dark Tower film and how do the situational archetypes build the main character in The Dark Tower film.This study is typical library research with descriptive qualitative method. This study used archetype theory by Carl Gustav Jung (1942), Hero archetype by Joseph Campbell (2004), and also movie analysis.The results reveal that there are seven types of situational archetypes find in The Dark Tower film. This results consist of the Departure, the Initiation, and The Return. The departure describes how the characters introduced  as they are presented with and prepare for their journey. There is often a rite of passage or quest in which the hero must prove or in order to achieve their certain goals. It can be seen that the task in the film increase and the character may finish several tasks through the journey. While the character have the journey, the character will face the unpleasent life and pleasent life.Keywords: archetype study, situational archetype, the dark tower film